2016
DOI: 10.1080/17441692.2016.1168863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a male engagement intervention to transform gender norms and improve family planning and HIV service uptake in Kabale, Uganda

Abstract: Men's limited understanding of family planning (FP) and harmful cultural gender norms pose obstacles to women's FP use. Thirty-two model men called 'Emanzis' were recruited from the community in Kabale, Uganda to lead men from their peer group through a 10-session curriculum designed to transform gender norms and motivate men to engage in FP and HIV services. Cross-sectional surveys were conducted before (n = 1251) and after (n = 1122) implementation. The Gender Equitable Men (GEM) Scale was used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 41 publications
1
53
0
2
Order By: Relevance
“…Thus, men had less fear about the stigma associated with HIV testing and were more willing to communicate with female sexual partners about couples counseling and testing. Another recent study by Ghanotakis et al [55] in Uganda showed that using a 10-week curriculum with men focused on transforming gender norms improved men’s willingness to go to a health facility and willingness to test for HIV. Together, these findings suggest that gender transformative interventions may be a promising approach for addressing masculinity-related barriers and leveraging masculinity-related facilitators to increase men’s HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, men had less fear about the stigma associated with HIV testing and were more willing to communicate with female sexual partners about couples counseling and testing. Another recent study by Ghanotakis et al [55] in Uganda showed that using a 10-week curriculum with men focused on transforming gender norms improved men’s willingness to go to a health facility and willingness to test for HIV. Together, these findings suggest that gender transformative interventions may be a promising approach for addressing masculinity-related barriers and leveraging masculinity-related facilitators to increase men’s HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating male engagement in integrated FP and HIV service use, health‐seeking practices improved for men, especially condom use, HIV testing, and health facilities visits (Ghanotakis et al. ). Integrated services also played a role in the prevention of mother‐to‐child transmission of HIV—specifically by promoting access to FP and by understanding key populations’ SRH needs (FHI360 ; Ippoliti in this issue).…”
Section: Recent Research Initiatives On Service Integrationmentioning
confidence: 99%
“…Research on integrating HIV testing and counseling and family planning by community health workers indicated it is feasible and acceptable and provides an opportunity to increase HIV testing among family planning clients (Brunie et al 2016). In a study evaluating male engagement in integrated FP and HIV service use, health-seeking practices improved for men, especially condom use, HIV testing, and health facilities visits (Ghanotakis et al 2016). Integrated services also played a role in the prevention of motherto-child transmission of HIV-specifically by promoting access to FP and by understanding key populations' SRH needs (FHI360 2013; Ippoliti 2017 in this issue).…”
Section: Recent Research Initiatives On Service Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring healthy lives and promoting well-being for all at all ages is one of the key agendas adopted by the UN General Assembly for 2030 [12]. Gender-specific strategies for care delivery, health education, and research are key to achieving these goals, particularly in disease-burdened LMICs [9,[13][14][15]. A 2007 World Health Organization (WHO) review of interventions designed to involve men and boys in achieving gender equality and better health concluded that well-designed male involvement interventions would be more effective at improving men's attitudes and behaviors toward sexual and reproductive health and other health conditions [16].…”
Section: Introductionmentioning
confidence: 99%